PENINGKATAN KEMAMPUAN MANAJERIAL KEPALA SEKOLAH MELALUI MORNING BRIEFING DI SD NEGERI 3 WIROTAMAN KEC. AMPELGADING KAB. MALANG - Santoso, Uki (Universitas PGRI Adi Buana Surabaya, 2019)
Wirotaman Public Elementary School 3 Ampelgading District Malang Regency as a school where the writer is in charge for example, has 6 educators / teachers. In fact, these educators often show their lack of solidarity in dealing with various problems that arise within the school and outside the school. Based on the observation of the author, it was found that some of the problems faced by school residents were caused by misunderstandings due to lack of communication (miss communication). This can be one of the causes of less labor productivity / performance of educators and ultimately can affect student learning achievement as well. Considering these conditions, on this occasion the researcher intends to conduct a School Action Research (PTS) as an effort to improve the principal's managerial abilities through morning briefing activities. After the morning briefing activities, there appeared to be an increase in the number of activity participants who agreed to the implementation of morning briefing activities, in addition if at the beginning of the morning breading the majority of the participants seemed still confused and awkward, then in the morning briefing activities in the sessions Furthermore, the participants of the activity seemed to be more free in expressing their ideas and thoughts in order to discuss various problems related to the condition of the school.